Fungal Alpha-Galactosidase from Pseudobalsamia microspora Capable of Degrading Raffinose Family Oligosaccharides - Yang, Dongxue; Tian, Guoting; Du, Fang; Zhao, Yongchang; Zhao, Liyan; Wang, Hexiang; Ng, Tzi Bun (Applied biochemistry and biotechnology, 2015)
An alpha-galactosidase was purified from Pseudobalsamia microspora (PMG) to 1224.1-fold with a specific activity of 11,274.5 units/mg by ion-exchange chromatography and gel filtration. PMG is a monomeric protein with a molecular mass of 62 kDa as determined by SDS-PAGE and by gel filtration. Chemical modification using N-bromosuccinimide (NBS) resulted in a complete abrogation of the activity of PMG, suggesting that Trp is an amino acid essential to its activity. The activity was strongly inhibited by Hg²⁺, Cd²⁺, Cu²⁺, and Fe³⁺ ions. Three inner peptide sequences for PMG were obtained by liquid chromatography–tandem mass spectrometry (LC–MS–MS) analysis. When 4-nitrophenyl α-D-glucopyranoside (pNPGal) was used as substrate, the optimum pH and temperature of PMG were 5.0 and 55 °C, respectively. The Michaelis constant (K ₘ) value of the alpha-galactosidase on pNPGal was 0.29 mM, and the maximal velocity (V ₘₐₓ) was 0.97 μmol ml⁻¹ min⁻¹. Investigation by thin-layer chromatography (TLC) demonstrated its ability to hydrolyze raffinose and stachyose. Hence, it can be exploited in degradation of non-digestible oligosaccharides from food and feed industries.